Obesity-Induced Methylation of Osteopontin Contributes to Adipogenic Differentiation of Adipose-Derived Mesenchymal Stem Cells - Min Tang; Rui Chen; Hao Wang; Guowei Sun; Fan Yin; Beibei Liang; Yang Yang; Gaowa Sharen; Huafeng Wei; Xuyu Zhou; Gang Huang; Jian Zhao (Stem Cells International)
Obesity is a major risk factor for many chronic diseases, including diabetes, fatty livers, and cancer. Expansion of the adipose mass has been shown to be related to adipogenic differentiation of adipose-derived mesenchymal stem cells (ASCs). However, the underlying mechanism of this effect has yet to be elucidated. We found that osteopontin (OPN) is downregulated in ASCs and adipose tissues of obese mice and overweight human beings because of methylation on its promoter, indicating that OPN may affect the development of obesity. Silencing of OPN in wild-type ASCs promotes adipogenic differentiation, while reexpression of OPN reduced adipogenic differentiation in OPN−/− ASCs. The role of extracellular OPN in ASC differentiation was further demonstrated by supplementation and neutralization of OPN. Additionally, OPN suppresses adipogenic differentiation in ASCs through the C/EBP pathways. Consistent with these in vitro results, by intravenous injection of OPN-expressing adenovirus to the mice, we found OPN can delay the development of obesity and improve insulin sensitivity. Therefore, our study demonstrates an important role of OPN in regulating the development of obesity, indicating OPN might be a novel target to attenuate obesity and its complications.